[Sydney International Exhibition : programs and invitations ephemera material collected by the National Library of Australia].
Material in the Programs and invitations ephemera collection includes invitations to official events, dinner invitations honouring visiting dignitaries, dance cards, award presentations, openings, commemorative and sporting programs. Some programs and invitations may also include menus.
The Sydney International Exhibition was held from 17 September 1879 to 20 April 1880.
Keywords: Exhibitions -- New South Wales -- Sydney -- Miscellanea; Printed ephemera -- Australia; Invitation cards -- Australia; Programs -- Australia; Australian